Mixed Electrical–Chemical Synapses in Adult Rat Hippocampus are Primarily Glutamatergic and Coupled by Connexin-36 - Hamzei-Sichani, Farid; Davidson, Kimberly G.; Yasumura, Thomas; Janssen, William G.; Wearne, Susan L.; Hof, Patrick R.; Traub, Roger D.; Gutierrez, Rafael; Ottersen, Ole P.; Rash, John E. (Frontiers in Neuroanatomy, 2012)
Dendrodendritic electrical signaling via gap junctions is now an accepted feature of neuronal communication in the mammalian brain, whereas axodendritic and axosomatic gap junctions have rarely been described. We present ultrastructural, immunocytochemical, and dye-coupling evidence for “mixed” (electrical/chemical) synapses in adult rat hippocampus on both principal cells and interneurons. Thin-section electron microscopic images of small gap junction-like appositions were found at mossy fiber (MF) terminals on thorny excrescences of CA3 pyramidal neurons (CA3pyr), apparently forming glutamatergic mixed synapses. Lucifer Yellow injected into four weakly-fixed CA3pyr was detected in MF axons that contacted the injected CA3pyr, supporting gap junction-mediated coupling between those two types of principal cells. Freeze-fracture replica immunogold-labeling revealed diverse sizes and morphologies of connexin36-containing gap junctions throughout hippocampus. Of 20 immunogold-labeled gap junctions, seven were large (328-1140 connexons), three of which were consistent with electrical synapses between interneurons; but nine were at axon terminal synapses, three of which were immediately adjacent to distinctive glutamate receptor-containing postsynaptic densities, forming mixed glutamatergic synapses. Four others were adjacent to small clusters of immunogold-labeled 10-nm E-face intramembrane particles, apparently representing extrasynaptic glutamate receptor particles. Gap junctions also were on spines in stratum lucidum, stratum oriens, dentate gyrus, and hilus, on both interneurons and unidentified neurons. In addition, one putative GABAergic mixed synapse was found in thin section images of a CA3pyr, but none found by immunogold-labeling were at GABAergic mixed synapses, suggesting their rarity. Cx36-containing gap junctions throughout hippocampus suggest the possibility of reciprocal modulation of electrical and chemical signals in diverse hippocampal neurons.